2021
DOI: 10.15420/aer.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Criteria for Differentiating Left from Right Idiopathic Outflow Tract Ventricular Arrhythmias

Abstract: Idiopathic ventricular arrhythmias are ventricular tachycardias or premature ventricular contractions presumably not related to myocardial scar or disorders of ion channels. Of the ventricular arrhythmias (VAs) without underlying structural heart disease, those arising from the ventricular outflow tracts (OTs) are the most common. The right ventricular outflow tract (RVOT) is the most common site of origin for OT-VAs, but these arrhythmias can, less frequently, originate from the left ventricular outflow tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The obtained classification results had a similar level of accuracy than clinical algorithms used in the SOO prediction (Anderson et al, 2019;Mariani et al, 2021). From these results, we have been able to conclude that, although extracting signal features from ECG seems to be the best approach, there is not a large improvement with respect to simply use raw data as features (the potential of the signal at ten equally spaced time points), provided that all signals are aligned.…”
Section: Discussionsupporting
confidence: 52%
“…The obtained classification results had a similar level of accuracy than clinical algorithms used in the SOO prediction (Anderson et al, 2019;Mariani et al, 2021). From these results, we have been able to conclude that, although extracting signal features from ECG seems to be the best approach, there is not a large improvement with respect to simply use raw data as features (the potential of the signal at ten equally spaced time points), provided that all signals are aligned.…”
Section: Discussionsupporting
confidence: 52%
“…31,32 However, the complex anatomy of the outflow tract, overlapping common sites of PVC origin, and potential factors such as cardiac rotation, lead positions, and preferential conduction of PVCs may limit the efficacy of typical surface ECG criteria. 31,33 Our study demonstrated significant clinical value of the LF/HF ratio in identifying the originating foci of OT-PVCs, which was independent of cardiac anatomy. Therefore, the LF/HF ratio may provide additional value to existing ECG criteria and algorithms in the differentiation between RVOT-PVCs and LVOT-PVCs.…”
Section: Discussionmentioning
confidence: 65%
“…The differences of vector ratios and QRS morphologies are maximized in an anteroposterior dimension. 12 The electroanatomical considerations can constitute a logical explanation for the principle of most ECG algorithms, including TZ index. 4 However, the posteriorseptal of RVOT is directly anterior to the right coronary cusp (RCC).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given that the electrical cardiac depolarizing vector moving away from (for RVOT) or towards (for LVOT) the anterior chest wall. The differences of vector ratios and QRS morphologies are maximized in an anteroposterior dimension 12 . The electroanatomical considerations can constitute a logical explanation for the principle of most ECG algorithms, including TZ index 4 .…”
Section: Discussionmentioning
confidence: 99%